(untitled) (Світ фінансів, 2017)
Кізима Т. О. Управління фінансами домашніх господарств: теоретико-прагматичні аспекти. Досліджено вплив макро- і мікроекономічного середовища на управління фінансами домашніх господарств та охарактеризовано основні методи й інструменти управління фінансами домашніх господарств у сучасних умовах вітчизняної економіки. Kizyma T. Management of households finance: theoretic and pragmatic aspects. The infl uence of macro-and microeconomic environment to the management of households finance is investigated, and the basic methods and instruments of the management of households finance in the modern terms of the domestic economy are described.